THE SUBJECT AREA OF ACCOUNTING IN ITS INSTITUTIONAL THEORY (INNOVATIVE ECONOMY, 2026)
Zhuk V.М. THE SUBJECT AREA OF ACCOUNTING IN ITS INSTITUTIONAL THEORYPurpose. The aim of the article is to review the subject area of accounting when considering it in the status of a socio-economic institution and to substantiate the directions of its institutional enrichment in the context of modern challenges in the development of science, the profession, and the transformation of the economy.Methodology of research. The methodological foundation of this study is the dialectical method of cognition, which enables an examination of the subject area of accounting in terms of its development, interrelationships, and contradictions within the context of institutional theory. General scientific and special methods were used in the research process, including induction and deduction – to generalize theoretical propositions and establish the logic of the research; the systemic approach – for a comprehensive analysis of accounting as a socio-economic institution; the modeling method – for constructing conceptual representations of the transformation of its subject area; analysis and synthesis – for identifying structural elements and generalizing scientific approaches; the monographic method – for an in-depth study of scientific works on the subject under investigation; the abstract and logical method – for theoretical generalization, formulation of conclusions, and identification of directions for further research. The information base consisted of scientific works by leading domestic and foreign scholars, professional experience, and the author’s observations.Findings. It is proven that the narrow interpretation of the subject of accounting as a reflection of the facts of economic life no longer corresponds to the modern level of development of accounting science and practice and weakens the academic status of accounting in the system of economic sciences. It is substantiated that attempts to expand the subject only by adding new objects of reflection do not eliminate the theoretical crisis, but, on the contrary, dilute its scientific essence. The author proposes a deductive model of institutional enrichment of the subject of accounting, which proceeds from a qualitative change in its functional demand: from the service function of management to the fulfillment of a broader socio-economic mission. It was determined that accounting, as an institution, is designed to ensure trust, understanding, and manageability of socio-economic spaces through the professional interpretation of the facts and phenomena of the lives of business entities.Originality. A new approach to defining the subject of accounting based on institutional theory is substantiated. The article proposes interpreting the subject of accounting not as a technique for reflecting economic transactions, but as a study of the nature of accounting and the information that supports trust, understanding, and the manageability of socio-economic spaces. The idea of deductive modeling of the subject area of accounting has been further developed.Practical value. The proposed provisions can be used to update the modern accounting paradigm, strengthen its academic status, develop professional education, and form conceptual accounting models capable of integrating financial, non-financial, social, and environmental aspects of enterprise activities.Key words: accounting, subject of accounting, institutional theory of accounting, socio-economic institute, professional judgment, accounting functions, accounting paradigm, accounting and information support.
Keywords: accounting; subject of accounting; institutional theory of accounting; socio-economic institute; professional judgment; accounting functions; accounting paradigm; accounting and information support